THE EXPERIENCE OF AN AGROECOLOGICAL SCHOOL GARDEN AS AN INTERACTIVE AND CREATIVE HEALTH PROMOTION STRATEGY - Natália Gebrim Doria; Denise Eugênia Pereira Coelho; Mariana Tarricone Garcia; Helena Akemi Wada Watanabe; Cláudia Maria Bógus (Universidade do Estado do Rio de Janeiro, 2017)
The school is an important place for the establishment of links between health and education, and it is also a suitable tool for Health Promotion. School gardens have emerged as innovative strategies with great potential for the development of health and nutrition issues. The objective of this study was to analyze a school garden as a health promotion strategy from the students' perspective. The subjects of this study were 10- and 11-year-old students (n=49) who were asked to draw a picture followed by an individual report about their experiences in the school garden, a method known as draw-and-tell. The analysis of these reports allowed to pinpoint categories relative to Health Promotion principles, such as equity, social participation, empowerment and sustainability, and personal skills development, as well as Nutrition Education and Food and Nutrition Security. School gardens are a powerful pedagogical strategy for Health Promotion. School gardens may also integrate actions in food and nutrition education and environmental education, through creative and interactive activities that stimulate the children's involvement. DOI: 10.12957/demetra.2017.23788